Sodium/Glucose Cotransporter 2 Inhibitors and the Risk of Diabetic Ketoacidosis: An Example of Complementary Evidence for Rare Adverse Events. Issue 8 (6th March 2021) - Alkabbani, Wajd; Pelletier, Ryan; Gamble, John-Michael
Abstract: Evidence from observational studies may be considered complementary to that of randomized controlled trials (RCTs), particularly when assessing rare outcomes of drug therapies. Sodium/glucose cotransporter 2 (SGLT-2) inhibitors are a novel class of antidiabetic agents that have been linked to an increased risk of diabetic ketoacidosis (DKA). We conducted a systematic review and separately meta-analyzed data from RCTs ( n  = 18; 2013–2019) and cohort studies ( n  = 7; 2017–2020) to assess the consistency of the magnitude of association between SGLT-2 inhibitors and DKA risk. We illustrate the strengths and weaknesses of the 2 designs. Results from RCTs and observational studies consistently showed almost a doubling in the risk of DKA among patients using an SGLT-2 inhibitor as compared with placebo or an active comparator. In a random-effects model, the pooled relative risk was 2.08 (95% confidence interval (CI): 1.28, 3.40) from placebo-controlled RCTs and 0.82 (95% CI: 0.25, 2.68) from active-comparator RCTs. The pooled adjusted hazard ratio from observational studies was 1.74 (95% CI: 1.28, 2.38). Notably, the 2 designs complement each other in several domains, including external and internal validity and power. This demonstrates a need for more comprehensive evidence when assessing rare adverse events for both sources.